Smutty wheat in swine diets - Allee, G.L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Smutty wheat substituted for milo in diets for pigs from 20-60 pounds did not affect pig performance.
Keywords: Swine; Smutty wheat; Milo